1996
DOI: 10.1016/s0960-9822(02)00606-1
|View full text |Cite
|
Sign up to set email alerts
|

Human and mouse homologs of the Saccharomyces cerevisiaeRAD54 DNA repair gene: evidence for functional conservation

Abstract: The tissue-specific expression of mHR54 is consistent with a role for the gene in recombination. The complementation experiments show that the DNA repair function of Rad54 is conserved from yeast to humans. Our findings underscore the fundamental importance of DNA repair pathways: even though they are complex and involve multiple proteins, they seem to be functionally conserved throughout the eukaryotic kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
99
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 49 publications
5
99
1
Order By: Relevance
“…19 Vertebrate homologues of these genes have been recently identified. [20][21][22] The high degree of sequence conservation from yeast to man and the similarity of in vitro biochemical function suggested that the vertebrate homologues were also involved in homologous recombination. RAD51, a eukaryotic homologue of E. coli recA, seems to play a central role in the process with its DNA pairing and strand exchange activities.…”
Section: Correspondence: Acg Porter This Paper Is Dedicated To the Mementioning
confidence: 99%
“…19 Vertebrate homologues of these genes have been recently identified. [20][21][22] The high degree of sequence conservation from yeast to man and the similarity of in vitro biochemical function suggested that the vertebrate homologues were also involved in homologous recombination. RAD51, a eukaryotic homologue of E. coli recA, seems to play a central role in the process with its DNA pairing and strand exchange activities.…”
Section: Correspondence: Acg Porter This Paper Is Dedicated To the Mementioning
confidence: 99%
“…Hybridization was performed overnight at 658C in 0.5 M NaPO 4 (pH7.2), 1 mM EDTA, 7% SDS and 1% bovine serum albumin, followed by washing three times for 30 min at 658C in 40 mM NaPO 4 (pH 7.2), 1 mM EDTA and 1% SDS. Nucleotide sequence was determined using Sequenase sequencing kit (Amersham) Figure 2 Multiple sequence alignment comparing the predicted helicase motifs of RAD54B to those of hRAD54, S. pombe RAD54 (SpRAD54) and ScRAD54 (Kanaar et al, 1996). Amino acid positions are shown on the left.…”
mentioning
confidence: 99%
“…Furthermore, this sequence is well conserved in the SNF2 superfamily regardless of species and subfamily. Asn at codon 593 is conserved in SNF2 (Laurent et al, 1991), MOT1 (Davis et al, 1992), BRM (Tamkun et al, 1992), ERCC6 (Troelstra et al, 1992), STH1 (Clark et al, 1992), FUN30 (Laurent et al, 1992) and RAD54 (Kanaar et al, 1996) throughout evolution from yeast to human. Asp at codon 418 is also at a conserved position ( Figure 6b).…”
mentioning
confidence: 99%
“…Two Rad54 homologous proteins have been found in different eukaryotic species (29). The human hRad54 protein has 68% similarity with ScRad54 protein.…”
mentioning
confidence: 99%